2014
DOI: 10.1371/journal.pone.0104988
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sphingolipids Reflect the Severity of Chronic HBV Infection and Predict the Mortality of HBV-Acute-on-Chronic Liver Failure

Abstract: Patients with HBV-acute-on-chronic liver failure (HBV-ACLF) have high mortality and frequently require liver transplantation; few reliable prognostic markers are available. As a class of functional lipids, sphingolipids are extensively involved in the process of HBV infection. However, their role in chronic HBV infection remains unknown. The aim of this study was to determine the serum sphingolipid profile in a population of patients with chronic HBV infection, paying special attention to exploring novel progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The increased DAG and ceramide could mediate insulin resistance, oxidative stress, apoptosis, and endoplasmic reticulum stress, which are associated with lipotoxic liver injury in NASH 19 22 . Interestingly, our study found decreased serum total lipids, neutral lipids (TAG, DAG, CE), and sphingolipids (Cer, SM) in the CHB without NAFLD group, indicating that chronic active HBV infection may be inversely associated with hyperlipidemia and insulin resistance and may play beneficial roles on lipid profiles 20 , 21 , 23 , 24 . Increasing epidemiological studies have shown that chronic HBV infection is inversely associated with the metabolic syndrome and its some components 6 8 , 25 , 26 .…”
Section: Discussionmentioning
confidence: 54%
“…The increased DAG and ceramide could mediate insulin resistance, oxidative stress, apoptosis, and endoplasmic reticulum stress, which are associated with lipotoxic liver injury in NASH 19 22 . Interestingly, our study found decreased serum total lipids, neutral lipids (TAG, DAG, CE), and sphingolipids (Cer, SM) in the CHB without NAFLD group, indicating that chronic active HBV infection may be inversely associated with hyperlipidemia and insulin resistance and may play beneficial roles on lipid profiles 20 , 21 , 23 , 24 . Increasing epidemiological studies have shown that chronic HBV infection is inversely associated with the metabolic syndrome and its some components 6 8 , 25 , 26 .…”
Section: Discussionmentioning
confidence: 54%
“…15 It is interesting to find the different kinds of sphingolipids in our previous findings related to the different causes and disease status. Additionally, it is confirmed that pathogens need to exploit lipid rafts, which sphingolipids are rich in, to get into the host cells 7,10 and proficient virus replication is crucially supported by lipid biosynthesis.…”
Section: Discussionmentioning
confidence: 94%
“…The HPLC-MS/ MS methodology used in this study was described in our previous report. 15 Sphingolipidomic assays were performed at the Institute of Materia Medica, Peking Union Medical College (Beijing, China).…”
Section: Hplc-ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the pathological processes of AD are thought to include the initial inflammatory response, degradation and destruction of vascular wall components and their release into the peripheral blood, and activation of the coagulation mechanism [11]. Therefore, recent identification of early peripheral blood biomarkers for AD has focused on markers for vascular endothelial injury and repair and inflammatory reactions in the early stage of the disease [12, 13]. The currently reported peripheral blood biomarkers for AD are all protein macromolecules, such as smooth muscle myosin heavy chain (smMHC), creatine kinase-BB (CK-BB), D-dimer, matrix metalloproteinases (MMPs), and elastin [14-16].…”
Section: Introductionmentioning
confidence: 99%